Systematic review documents limited empirical support for the practical application of the Theory of Mind model of ASD. Issue 3 (1st October 2016) - Paynter, Jessica M.; Keen, Deb; Rose, Veronica J.
Abstract : This review provides a summary and appraisal commentary on the treatment review by Fletcher-Watson, S., McConnell, F., Manola, E., & McConachie, H. (2014). Interventions based on the Theory of Mind cognitive model for autism spectrum disorder (ASD). Cochrane Database of Systematic Reviews 2014, Issue 3, Art. No. Cd008785. doi:10.1002/14651858.CD008785.pub2 Source of funding and declaration of interests: The authors report no conflicts of interest.